Han Rosie

Tính giá trị của các biểu thức sau biết x+y+1=0

N=x^2(x+y)-y^2(x+y)+x^2-y^2+2(x+y)+3

Nguyễn Lê Phước Thịnh
31 tháng 3 2021 lúc 23:11

Ta có: x+y+1=0

nên x+y=-1

Ta có: \(N=x^2\left(x+y\right)-y^2\left(x+y\right)+x^2-y^2+2\left(x+y\right)+3\)

\(=\left(x+y\right)\left(x^2-y^2\right)+\left(x^2-y^2\right)+2\left(x+y\right)+3\)

\(=\left(x^2-y^2\right)\left(x+y+1\right)+2\left(x+y\right)+3\)

\(=\left(x^2-y^2\right)\cdot0+2\cdot\left(-1\right)+3\)

=-2+3=1

.


Các câu hỏi tương tự
buidangduong
Xem chi tiết
trần ngọc anh
Xem chi tiết
Thai Hung Vu
Xem chi tiết
Lê Hạnh Nguyên
Xem chi tiết
Lê Nhật Minh
Xem chi tiết
Snow Moon
Xem chi tiết
Phải Không Vầy
Xem chi tiết
Lan Phương Nguyễn
Xem chi tiết
Trần Tuấn Anh
Xem chi tiết